Integration of RISHA and Eco-Damper Prevents Earthquake Damage to Houses - Sugiarto, Amalia Rizka; Saripudin, Mochamad Malik Abdulah (Semesta Teknika, 2024)
This research introduces an eco-damper building concept integrating Simple Healthy Instant House (RISHA) technology with reclaimed vehicle tires to enhance earthquake resistance in Indonesian residential buildings. Many earthquake-resistant building designs currently focus on structural reinforcement but overlook sustainable materials and cost-effectiveness, creating a gap in addressing environmental and disaster resilience. This study addresses this gap through a literature review and a conceptual design approach, identifying RISHA technology's strengths, limitations, and potential applications combined with eco-damper systems. The research found that integrating RISHA and recycled rubber from vehicle tires offers a comprehensive solution that enhances earthquake resistance while promoting sustainability and energy efficiency. The eco-damper system introduces a novel approach compared to earthquake-resistant technologies and contributes positively to environmental preservation by utilizing waste materials. However, one of the identified challenges is ensuring consistent material quality from used tires and the need for proper disposal or repurposing of other waste materials associated with this method. This study significantly contributes to disaster risk reduction in Indonesia. At the same time, the eco-damper concept also shows potential scalability for use in other earthquake-prone regions, offering a sustainable and adaptable solution.